Physiotherapeutic treatment in patients with hip dysplasia - Anna Lewandowska; Dorota Ratuszek-Sadowska; Monika Kuczma; Waldemar Kuczma; Joanna Simińska; Wojciech Hagner (Journal of Education, Health and Sport, 2018)
Congenital and acquired musculoskeletal diseases in children are often unnoticed and develop asymptomatically and without pain. Left untreated and earlier diagnosed, they deepen, leading to early degenerative changes and subsequent disability. Developmental hip dysplasia, i.e. disturbances in the formation and development of the infant's hip, occurs in Poland in about 4% of the newborn population. The appearance and further development of pathological changes of the hip may occur in the intrauterine period, during delivery or in later childhood. Detection of a defect in the first week of a child's life allows for early treatment and healing. Therefore, it is important to carefully screen hip joints. The aim of the work is to present physiotherapeutic methods used in the treatment of hip dysplasia.